2018
DOI: 10.1080/15622975.2018.1433878
|View full text |Cite
|
Sign up to set email alerts
|

The role of the gut microbiota in schizophrenia: Current and future perspectives

Abstract: In this review, the gut microbiota and epigenetic mechanisms were considered as key regulators, revealing a potential new aetiology of schizophrenia. Likewise, continuous technological advances (e.g. culturomics), aimed at the microbiota-gut-brain axis generate new evidence on this concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 115 publications
0
21
0
1
Order By: Relevance
“…On the contrary, patients with schizophrenia, who were significantly likelier to smoke, had decreased abundance of Clostridium ( 56 ) ( Figure 6 and Table 2 ). Enterobacteriaceae were increased in chronic schizophrenia patients ( 41 ) ( Figure 6 and Table 2 ), which would be in line with possible tobacco usage; however, smoking status was not reported within that study.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…On the contrary, patients with schizophrenia, who were significantly likelier to smoke, had decreased abundance of Clostridium ( 56 ) ( Figure 6 and Table 2 ). Enterobacteriaceae were increased in chronic schizophrenia patients ( 41 ) ( Figure 6 and Table 2 ), which would be in line with possible tobacco usage; however, smoking status was not reported within that study.…”
Section: Discussionmentioning
confidence: 54%
“…Most recently, a study demonstrated that mice receiving feces from individuals with schizophrenia showed a behavioral phenotype that is consistent with that have been seen in animal models of schizophrenia and depression (40). This finding demonstrates that a constituent of the fecal matter have effect of brain function and behavior of the host and strengthen the suggestion that the microbiome might contribute to behavioral symptoms in psychosis (41).…”
Section: Introductionmentioning
confidence: 53%
“…et al, 2017 ; Yolken and Dickerson, 2017 ), and microbiota regulation probably alleviates the disorder ( Hamdani et al, 2015 ; Dickerson et al, 2017 ). Schizophrenia is related with the dysfunction of microbiota–gut–brain axis ( Nemani et al, 2015 ; Rodrigues-Amorim et al, 2018 ; Shen et al, 2018 ), and improving the gut-brain and immune functions by targeting the microbiota could possibly produce beneficial effects ( Davey et al, 2013 ; Tomasik et al, 2015 ; Dickerson et al, 2017 ). Additionally, patients subjected to neurodevelopmental disorders, including autism spectrum disorders (ASD) and attention deficit hyperactivity disorder (ADHD), possess abnormal gut microbiota ( Mayer et al, 2014b ; Aarts et al, 2017 ; Strati et al, 2017 ), while correcting the microbiota abnormalities in a timely manner probably improves the development of the brain and behavior and has remedial effects ( Borre et al, 2014 ; Partty et al, 2015 ; Kang et al, 2017 ; Doenyas, 2018 ; Yang et al, 2018 ).…”
Section: Gut Microbiota Gut-brain and Gut-brain Psychologymentioning
confidence: 99%
“…Also, recent data have shown a high correlation of IgG-mediated antibodies between the periphery and cerebral spinal fluid in schizophrenia but not healthy controls, particularly AGA IgG suggesting that these antibodies may be crossing the blood-brain barrier with resulting neuroinflammation [25]. Schizophrenia has been extensively associated with other abnormal translational markers, suggesting an increased gut permeability in this illness [23,[25][26][27][28][29]. More than one in five SZ patients are identified with metabolic syndrome [30], and one-third with chronic low-grade peripheral inflammation [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%